Signalosomes as Therapeutic Targets - Negro, Alejandra (2008)
Cardiac hypertrophy is the predominant compensatory response of the heart to a wide variety of biomechanical stressors, including exercise, hypertension, myocardial infarction, intrinsic cardiomyopathy or congenital heart disease. Although cardiac hypertrophy can maintain cardiac output in response to elevated wall stress, sustained cardiac hypertrophy is often accompanied by maladaptive remodeling which can ultimately lead to heart failure. Cultured cardiac myocytes, transgenic and knock-out animal models, and pharmacological studies have not only revealed key molecules involved in hypertrophic signaling, but have also highlighted the redundancy in the hypertrophic signaling cascade. Currently, the majority of existing therapies for inhibition of pathologic cardiac hypertrophy and heart failure target molecules on the surface of cardiac myocytes, such as G-protein coupled receptors (GPCRs) and ion channels. Because these molecules are upstream of multiple intracellular signaling pathways, however, current therapy is often accompanied by significant off-target effects and toxicity. More recently, research has focused on identifying the intracellular effectors of these signaling cascades in the hope that more selective drugs may be rationally designed for therapeutic intervention. Within the cardiac myocyte, the formation of discrete multimolecular complexes, or ‘signalosomes’, is an important mechanism for increasing the specificity and efficiency of hypertrophic signal transduction. In response to extracellular stimuli, these signalosomes can alter gene and protein expression, cell size, and chamber remodeling, such as in the case of the signalosomes formed by the mAKAPβ and AKAP-lbc scaffold proteins. A better understanding of the basic molecular mechanisms regulating the compartmentation and scaffolding of signaling molecules could lead to the development of new clinical tools that may prevent the development of heart failure and minimize negative impacts on physiological processes.